LoRa‐aided outdoor localization system: RSSI or TDoA? - Yoshitome, Eric Hideo; Cruz, João Vitor Rodrigues; Monteiro, Marcos Eduardo Pivaro; Rebelatto, João Luiz (Internet technology letters, 2022)
Internet of Things (IoT) is a hot research topic, and typically involves communication between small devices in order to sense, react, and reinvent our way of living. To this end, the localization of such small devices is of great importance for most applications. Between the many applications of IoT, there are those which require low power communication between long ranges, which are entitled Low Power Wide Area (LPWA) communications. One of the main LPWA technologies is the Long Range (LoRa), which does not support native localization. In order to overcome such a problem, a possible approach is to use the Global Positioning Systems (GPS), but it can be costly when aiming for cheaper and simpler devices. This paper evaluates the accuracy of a LoRa‐aided outdoor localization system when locating GPS‐free Target Nodes (TN) through the use of Anchor Nodes (AN) with known positions. Two different indicators are used, namely the Received Signal Strength Indicator (RSSI) and the Time Difference of Arrival (TDoA). Our results indicate that, in general, TDoA presents an improved accuracy over RSSI, with errors ranging from 66 to 253 m in the considered scenario.